Clinical use of color Doppler ultrasonography to predict and evaluate the collateral development of two common revascularizations in patients with moyamoya disease - Wang, Jing-Zhe; Mu, Jie; Zhang, Dong; Zheng, Shuai; Zhu, Xun; Wei, Xi (Frontiers in Neurology, 2022)
Objective To explore the value of color Doppler ultrasonography (CDU) to predict preoperatively and evaluate postoperatively the collateral development of two common revascularizations in patients with moyamoya disease (MMD). Methods we prospectively enrolled 49 patients with MMD who underwent unilateral superficial temporal artery (STA) -middle cerebral artery (MCA) anastomosis or encephalo-duro-arterio-synangiosis (EDAS). The parameters of the extracranial arteries, including STA, internal carotid artery (ICA), external carotid artery (ECA), vertebral artery (VA), were performed before and at 3-6 months after surgery. DSA results were used to assess the surgical collateral development. Results To predict the good collateral development before STA-MCA anastomosis, the pre-operative D > 1.75mm in the STA had the highest area under the Receiver Operating Characteristic curve (AUC). To predict the good collateral development before EDAS, the pre-operative EDV > 12.00cm/s in the STA had the highest AUC. To evaluate the good collateral development after STA-MCA anastomosis, the postoperative EDV > 16.50 cm/s in the STA had the highest AUC. To evaluate the good collateral development after EDAS, an increase of D of 0.15mm in the STA had the highest AUC. Logistic regression analysis showed the preoperative RI and EDV in the STA was highly correlated with the collateral development. Besides, the preoperative RI was the independent risk factor for the collateral development. Conclusion CDU could predict preoperatively and evaluate postoperatively the collateral development of STA-MCA anastomosis and EDAS surgery by detecting ultrasound parameters of the STA.